A width of cut analysis on the performance of a rotary strip tiller - Ahmad, Desa (Universiti Pertanian Malaysia, 1986)
This paper describes a soil bin study on the effect of blade widths upon rotary tiller performance which forms part of the research undertaken by the author on rotary tillage. Blades used were designed and tested at several forward and rotor speed combinations using a single rotor flange. Results obtained for each combination of forward and rotor speed show significant increase in power consumption as cutting width increased. In terms of specific power, however, the wider the cutting widths the lower the specific power values. The highest degree of soil pulverization was caused by the smallest width at the smallest bite length.